A Contextual Approach On The Concept Of Sami'a In The Hadith Text Of Sahih Al-Bukhariyy - Juliyana Junaidi (Universiti Sains Islam Malaysia, 2024)
Hadith understanding is one of the crucial aspects in appreciating the sunnah of Prophet Muhammad PBUH. As the second most reliable source after al-Quran, hadith requires a special attention in its interpretation. Prominent Muslin1 scholars have already highlighted the significance of hadith understanding as well as expounding its approaches. Among the principles of comprehending hadith is understanding in a contextual method. However, the contextual approach of hadith understanding can only be utilized in Hadith al-Mutaghayyirat amd not applicable to Hadith al-Thawabit. In addition, books of hadith comilation offer different concepts based on the methods used by the hadith compiler.However, it does not have higher level of concepts that cover the classifications. This study aims to investigate existing approaches of hadith understanding and to propose an enhancement in the methods of hadith understanding. Besides, it also aims to propose concepts based on contextual understanding of hadith. This study used qualitative method through document analysis in the data collection process and thematic analysis in the data analysis. The matan of Hadith WQawli containing the words sami’a from Sahih al-Bukhariyy will be analysed based on several commentary books of hadith and other supporting sources. The aspects of 5W1H which involve What, Who, Where, Why, When and How were suggested to understand hadith in a contextual way. Besides, concepts on hadith were developed based on the proposed classifications of the hadith according to its contextual understanding. Results indicate that the aspects of 5W1H could be applied as a contextual approach in hadith understanding. Apart from that, Hadith Qawli with words sami’a in Sahih al-Bukhariyy could be generalized into two major concepts which are the concept of Belief and Shari’ah. Therefore, this study could enhance the approaches in contextual hadith understanding.